Enhanced stripe rust resistance obtained by combining Yr30 with a widely dispersed, consistent QTL on chromosome arm 4BL - Shengjie Liu; Xiaoting Wang; Yayun Zhang; Yangang Jin; Zhonghua Xia; Mingjie Xiang; Shuo Huang; Linyi Qiao; Weijun Zheng; Qingdong Zeng; Qilin Wang; Rui Yu; et al. (Springer, 2022)
Key message: YrFDC12 and PbcFDC, co-segregated in chromosome 4BL, and significantly interacted with Yr30/Pbc1 to enhance stripe rust resistance and to promote pseudo-black chaff development. Abstract: Cultivars with durable resistance are the most popular means to control wheat stripe rust. Durable resistance can be achieved by stacking multiple adult plant resistance (APR) genes that individually have relatively small effect. Chinese wheat cultivars Ruihua 520 (RH520) and Fengdecun 12 (FDC12) confer partial APR to stripe rust across environments. One hundred and seventy recombinant inbred lines from the cross RH520 × FDC12 were used to determine the genetic basis of resistance and identify genomic regions associated with stripe rust resistance. Genotyping was carried out using 55 K SNP array, and eight quantitative trait loci (QTL) were detected on chromosome arms 2AL, 2DS, 3BS, 4BL, 5BL (2), and 7BL (2) by inclusive composite interval mapping. Only QYr.nwafu-3BS from RH520 and QYr.nwafu-4BL.2 (named YrFDC12 for convenience) from FDC12 were consistent across the four testing environments. QYr.nwafu-3BS is likely the pleiotropic resistance gene Sr2/Yr30. YrFDC12 was mapped in a 2.1-cM interval corresponding to 12 Mb and flanked by SNP markers AX-111121224 and AX-89518393. Lines harboring both Yr30 and YrFDC12 displayed higher resistance than the parents and expressed pseudo-black chaff (PBC) controlled by loci Pbc1 and PbcFDC12, which co-segregated with Yr30 and YrFDC12, respectively. Both marker-based and pedigree-based kinship analyses revealed that YrFDC12 was inherited from founder parent Zhou 8425B. Fifty-four other wheat cultivars shared the YrFDC12 haplotype. These results suggest an effective pyramiding strategy to acquire highly effective, durable stripe rust resistance in breeding.